WATERSHED MORPHOMETRIC CLASSIFICATION ANALYSIS USING GEOGRAPHIC INFORMATION SYSTEM (GEOMATE Journal, 2020)
One of the important physical characteristics of watersheds is morphometry. Watershed shape is one the earth surface morphometric features. The watershed shape has a strong relation with the characteristic peak discharge and land erosion. Therefore, the watershed shape due to the strong relation between watershedshape and peak discharge and land erosion must be classified. Watershed shape can be classified based on morphometric analysis from the perspective of linear, areal, and relief aspects. In this paper the watershed located at Serayu-Bogowonto river basin was classified into four categories based on areal aspect. The areal aspects used to classify the watershed included Gravelius’s index, form factor, shape index, shape factor, circularity ratio, elongation ratio, and compactness coefficient. Four categories of watershed shapes (circular, oval, semi-oval, and elongated) were applied in this research. Seventeen watersheds at Serayu-Bogowonto river basin were selected as samples in the classification process. The Geographical Information System (GIS) technique was applied to generate watershed geometric properties such as, river length, watershed perimeter, area, diameter, and watershed length. Based on the analysis process, watersheds with broad and wide shape were difficult to classify. Such watersheds can be classified as circular, oval, semi-oval, and elongated. Finally, these watersheds can be classified under one category based on morphometric analysis results combined with the watershed figure. From the 17 watersheds, 5 were classified as circular, 3 as oval, 5 as semi-oval, and 4 aselongated shapes. GIS is a powerful tool for the analysis relating to watershed morphometric parameters.